Intensity Demodulation Based Fiber Sensor for Dynamic Measurement of Acoustic Wave and Lateral Pressure Simultaneously - Xin Fu; Ping Lu; Wenjun Ni; Li Liu; Hao Liao; Deming Liu; Jiangshan Zhang (IEEE Photonics Journal)
In this paper, we propose an intensity demodulation based fiber sensor for dual-parameters sensing of acoustic wave and lateral pressure. The sensor consists of a long period fiber grating (LPFG) inserted into a Sagnac interferometer (SI). The LPFG is kept straight and fixed on a polyethylene terephthalate membrane for acoustic detection. A tunable laser source (TLS) is utilized to illuminate the sensor. The acoustic wave will produce a time-varying intensity signal that consists of an alternating current (ac) component and a direct current (dc) component. The ac component contains the acoustic information, while the dc level is determined by the transmittance of the sensor in the static condition (without acoustic signal applied on the sensor). Since the lateral pressure induced wavelength shift of the SI will change the transmittance at the TLS wavelength, the dc level varies with different lateral pressure applied on the sensor. Therefore, the acoustic wave and lateral pressure can be demodulated, respectively, by monitoring the ac component and dc level in the output signal. In the experiment, output time-domain signals with 500 Hz ac components and different dc values are acquired when 500 Hz acoustic wave and different lateral pressure is applied on the sensor.